A novel forward osmosis reactor assisted with microfiltration for deep thickening waste activated sludge: performance and implication. (1st May 2021) - Yi, Xiawen; Zhong, Huihui; Xie, Ming; Wang, Xinhua
Highlights: A novel FO reactor assisted with MF for sludge thickening was developed. A deep thickening of WAS was achieved from approximately 7 to 50 g/L. An excellent water quality of FO membrane permeate was obtained. The flux decline of FO membrane was mainly due to membrane fouling. MLSS concentration significantly influenced the fouling mechanism of FO membrane. Abstract: Waste activated sludge (WAS) treatment has gained growing interests for its increasingly capacity and high process cost. Sludge thickening is generally the first process of the WAS treatment. However, traditional sludge thickening approach was restrained by large footprint, low thickening efficiency, and tendency of releasing phosphorus. Here, we reported a novel microfiltration (MF) membrane assisting forward osmosis (FO) process (MF-FO) for sludge thickening. The MF-FO reactor achieved a sludge thickening of the mixed liquor suspended solids (MLSS) concentration from approximately 7 to 50 g/L after 10-day operation. More importantly, the effluent quality after FO filtration was superior with total organic carbon (TOC), ammonia nitrogen (NH4 + -N), nitrate nitrogen (NO3 − -N) and total phosphorus (TP) of 1.94 ± 0.46, 0.02 ± 0.07, 4.55 ± 1.59 and 0.24 ± 0.26 mg/L, respectively. Additionally, the integration of MF membrane successfully controlled the salinity of the MF-FO reactor in a low range of 1.6-3.1 mS/cm, which mitigated the flux decline of FO membrane and thus prolonged the operating time. In this case, the flux decline of FO membrane in the MF-FO reactor was mainly due to the membrane fouling. Furthermore, the fouling layer on the FO membrane surface was a gel layer mainly composed of biofoulants and organic foulants when the MLSS concentration was less than 30 g/L, while it turned to a cake layer when the MLSS concentration exceeded 30 g/L. Results reported here demonstrated that the MF-FO reactor is a promising WAS thickening technology for its excellent thickening performance and high effluent quality of FO membrane. Graphical abstracts: Image, graphical abstract